2012
DOI: 10.1039/c2cc17015a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the translocation of peptides through nanopores by the application of an AC electric field

Abstract: The interaction of two peptides with the α-hemolysin pore was studied in the presence of a MHz AC field. For an α-helical peptide the proportion of bumping events increased with increasing AC field whereas for a linear peptide with no dipole moment only small changes in the event profiles were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…This result does not necessarily imply that the N‐terminal peptide was folded or aggregated, as its net charge is + 4, and, therefore, it will not be electrophoretically driven through the pore. It can, however, give rise to bumping events, owing to diffusion‐driven interactions with the pore . Surprisingly, on addition of Cu(II) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result does not necessarily imply that the N‐terminal peptide was folded or aggregated, as its net charge is + 4, and, therefore, it will not be electrophoretically driven through the pore. It can, however, give rise to bumping events, owing to diffusion‐driven interactions with the pore . Surprisingly, on addition of Cu(II) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the experimental side, it has been shown that the translocation of DNA through a nanochannel can be modulated by dynamically changing the cross-section of an elastomeric nanochannel device by applying mechanical stress [48][49][50][51][52]. Time-dependent driving force are also used in the translocation process [53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Since the size of fluid reservoirs is usually much larger than that of the nanopore, the local electric field within the nanopore is significantly higher than that in the fluid reservoir, resulting in slow particle motion within the fluid reservoir and high translocation velocity inside the nanopore. One of the major challenges in the nanopore-based technique is that DNA nanoparticles translocate through the nanopore too fast to be accurately detected [5,6,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Although one can reduce the voltage bias applied across the nanopore to reduce the electric field inside the nanopore and consequently slow down the DNA translocation, lower voltage bias will simultaneously reduce the capture rate of the nanopore and the magnitude of the current change, leading to lower throughput and read-out accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a relatively high voltage bias is typically applied across the nanopore in the nanoporebased DNA sequencing applications. To now, several methods have been proposed to slow down the DNA translocation through the nanopore to achieve higher read-out accuracy [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. They include increasing the solvent viscosity to increase the viscous drag force on the particle, lowering the fluid temperature to increase the fluid viscosity, adjusting salt concentration and/or salt type to modify the charge property of the nanopore by chemical functionalization of the nanopore or by an ionic field effect transistor, imposing a salt concentration gradient, utilizing optical tweezers, and conducting nanopores [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%